Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Motivasi Belajar - Dewi Jayanti; Susanti Susanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
This study aims to analyze and describe the efforts made by Islamic Religious Education teachers in increasing student learning motivation. The focus of this research is how teachers integrate Islamic religious values into the learning process in order to encourage students to be more enthusiastic and enthusiastic in learning. The research method used is a qualitative approach with in-depth interviews with several Islamic Religious Education teachers who have experience in managing student learning motivation. The results show that Islamic religious education applies various strategies to increase students' learning motivation. These strategies include using an interactive approach in teaching, using interesting learning media, and a personalized approach to understanding individual learning needs. Teachers also actively establish emotional relationships with students through open communication, providing positive feedback, and creating an inclusive classroom environment. In addition, this study also reveals that the application of Islamic religious values in daily life by teachers has a positive impact on students' learning motivation. Teachers who become role models in applying religious teachings in real actions encourage students to internalize these values and make them a motivation in learning.